Long-term Outcomes and Complications of Multilevel ACDF, Compared with Single-level ACDF, A Retrospective Study - Kuruvanich, Anusorn; Jitpun, Ekkapot; Tangviriyapaiboon, Teera (Thai Journal of Neurological Surgery, 2025)
Objective: To compare the clinical outcomes, radiological parameters, and complication incidence of patients who underwent anterior cervical discectomy and fusion (ACDF) to prove our hypothesis that multilevel ACDF did not have higher rate of complication than single level or 2-level ACDF. Methods: We conducted a retrospective review of 82 consecutive patients who underwent ACDF for treatment of cervical spondylosis at Neurological Institute of Thailand in 10 years (2006 – 2015) by single surgeon. Patients were divided into 3 group (1-level, 2-level and 3 or 4 level ACDF). The clinical courses, fusion rate, postoperative complications, and radiographical adjacent-level changes regarding each group were evaluated. Results: There is no statistical difference in restoration of cervical lordosis, and incidence of postoperative early and late complications between 1-level ACDF, 2-level ACDF and 3 or 4-level ACDF groups (P > 0.05). The 3 or 4-level ACDF group had more bleeding (P = 0.000) and longer length of stay in hospital (p = 0.002), with no clinically significant. Subgroup analysis of 3-level ACDF and 4-level ACDF had no statistical differences in all categories. Conclusion: This study showed that result of multilevel ACDF was not different from 1 or 2-level ACDF in all outcome parameters. Compared to previous systematic review of posterior approach, this study does not show different results and complications. Multilevel ACDF had no higher risk of surgery in comparison to 1 or 2-level ACDF.